2020
DOI: 10.3390/foods9050573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thawing and Frying Methods on the Formation of Acrylamide and Polycyclic Aromatic Hydrocarbons in Chicken Meat

Abstract: Air frying is commonly used as a substitute for deep-fat frying. However, few studies have examined the effect of air frying on the formation of potential carcinogens in foodstuffs. This study aimed to investigate the formation of acrylamide and four types of polycyclic aromatic hydrocarbons (PAHs) in air-fried and deep-fat-fried chicken breasts, thighs, and wings thawed using different methods, i.e., by using a microwave or a refrigerator, or by water immersion. The acrylamide and PAHs were analyzed by high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 32 publications
2
37
1
1
Order By: Relevance
“…Elfaitouri et al [ 97 ] investigated the effect of fat used for frying and showed that using the one with greater oxidative stability results in the formation of less acrylamide. The importance of the freshness of the frying oil and the formation of less acrylamide with the use of fresh oil was also confirmed by Lee et al [ 10 ]. The authors concluded that, regardless of the freshness of the fat used for frying, it is most advantageous not to use oil at all because of the acrylamide formation.…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 68%
See 1 more Smart Citation
“…Elfaitouri et al [ 97 ] investigated the effect of fat used for frying and showed that using the one with greater oxidative stability results in the formation of less acrylamide. The importance of the freshness of the frying oil and the formation of less acrylamide with the use of fresh oil was also confirmed by Lee et al [ 10 ]. The authors concluded that, regardless of the freshness of the fat used for frying, it is most advantageous not to use oil at all because of the acrylamide formation.…”
Section: Acrylamide In Microwave Heatingmentioning
confidence: 68%
“…Thanks to technological development and the use of both industrial and home-cooking techniques, the knowledge of the application of the thermal treatment to achieve specific food qualities, has increased. Numerous studies have shown that thermal treatment changes the physical and chemical structure of food [ 1 , 7 , 8 , 9 , 10 , 11 ]. Moreover, it is believed that not only heating temperature and time are the most important factors in the formation of hazardous compounds in foods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results indicated that the unsaturated fatty acids present in the frying oil promoted PAH production. The reason why air-fried samples exhibited lower acrylamide and total PAH contents than deep-fat-fried ones can therefore be attributed to the much lower oil content used [100].…”
Section: Effect Of Air Frying On Food Safetymentioning
confidence: 99%
“…In recent years, consumption of low-fat, low-calorie, high-protein chicken meat has increased significantly [1]. The quality of poultry meat depends on the production performance of the poultry.…”
Section: Introductionmentioning
confidence: 99%